Race, sex, and gender in contemporary women's theatre : the construction of "woman" - Brewer, Mary F. (Sussex Academic Press, 1999)
"Focusing on dramatic works by contemporary British and American playwrights, in conjunction with feminist political and theoretical texts, this book discusses feminist constructions of the category "Woman". It traces the ways in which mainstream feminist representations of gender are complicit with dominant racial and heterosexual ideologies. The plays addressed generate valuable insights as to how interpretations of "Woman" structure the political field and determine the standards used for interpreting Woman-as-Wife/Mother, Woman at Work, and Woman as Object and Subject." "A Conclusion details where women of difference should locate themselves for resistance and how feminists might go about establishing a progressive feminist politics and a women's movement that is able to accommodate differences of race, class, and sexuality."--Jacket